The Concept of Justice and Benefit for Perpetrators and Victims of Crime - Imamuddin; Mashabie Syamnur; Wardah Nur Syahira Sinaga (Jurnal Sahabat ISNU SU, 2024)
Crime is an inevitable social problem because it is related to individual behavior, social structure, economic inequality, and weak control of norms and laws. In the Indonesian positive legal system, particularly the Criminal Procedure Code (KUHAP), the retributive paradigm remains dominant, resulting in relatively marginalized victims and the right to redress not being systematically accommodated. This study examines criminal law enforcement from the perspective of Islamic justice, which places the principles of 'adl (justice) and maslahah (benefit) as the normative foundation. Qualitative research methods were used with a literature study approach and juridical-sociological analysis of laws and regulations, fiqh doctrine, and related literature. The research stages included secondary data collection, comparative analysis between the retributive and restorative paradigms, and synthesis of the concept of maqasid al-shari'ah in the context of victim recovery and perpetrator rehabilitation. The results indicate that the integration of the principles of restorative justice and maqasid can strengthen victim protection, encourage material and immaterial recovery, and provide a restorative orientation to sanctions that support social reintegration. The discussion emphasized the need for reform of judicial policies and practices to accommodate victim recovery mechanisms, officer training, and alternative sentencing policies based on maslahah (beneficial interests) in order to achieve social harmony.